2020
DOI: 10.14573/altex.2006262
|View full text |Cite
|
Sign up to set email alerts
|

Grouping of UVCB substances with new approach methodologies (NAMs) data

Abstract: One of the most challenging areas in regulatory science is assessment of the substances known as UVCB (unknown or variable composition, complex reaction products and biological materials). Because the inherent complexity and variability of UVCBs present considerable challenges for establishing sufficient substance similarity based on chemical characteristics or other data, we hypothesized that new approach methodologies (NAMs), including in vitro test-derived biological activity signatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(60 citation statements)
references
References 17 publications
5
55
0
Order By: Relevance
“…The lack of cardiotoxicity testing requirements is concerning, because epidemiological data suggest that about one-third of ischemic heart disease burden can be attributed to environmental exposures . In addition, there is emerging evidence from in vitro studies that environmental chemicals have the potential to affect human cardiomyocytes or pathways that are known to be important for cardiovascular health . Collectively, recent studies that examined dozens of environmental chemicals representative of a number of chemical classes serve as a proof of concept to elevate the concern to various regulatory agencies in the United States, European Union, and other countries .…”
Section: Introductionmentioning
confidence: 99%
“…The lack of cardiotoxicity testing requirements is concerning, because epidemiological data suggest that about one-third of ischemic heart disease burden can be attributed to environmental exposures . In addition, there is emerging evidence from in vitro studies that environmental chemicals have the potential to affect human cardiomyocytes or pathways that are known to be important for cardiovascular health . Collectively, recent studies that examined dozens of environmental chemicals representative of a number of chemical classes serve as a proof of concept to elevate the concern to various regulatory agencies in the United States, European Union, and other countries .…”
Section: Introductionmentioning
confidence: 99%
“…We selected these cell types because many of the environmental chemicals expected to be present in tested sediments are known to be associated with hepatotoxicity, neurotoxicity, cardiotoxicity, and vascular toxicity (see literature review of the effects of Superfund priority list chemicals on different organs in [ 20 ]). We have published methods for using iPSC-derived cells [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] to assess the toxicity of the individual chemicals [ 20 , 28 , 29 , 30 , 31 , 32 ], whole mixtures [ 11 , 16 ], and complex substances [ 33 , 34 ]. The reasons we chose iPSC-derived cells are because: (i) these cells are more physiological than immortalized cell lines and can be derived for different tissues/organs [ 35 ]; (ii) they can be obtained from the same individual(s) to enable highly reproducible experiments [ 36 ]; (iii) despite some limitations with the degree of maturation, these cells compare well to primary cells in terms of their function and expected organ-specific toxicity [ 35 , 37 , 38 ]; and (iv) a small number of iPSC-derived cell types can be as informative about hazard and safety margins as the larger set of in vitro models [ 33 ], or many ToxCast bioassays [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…We have published methods for using iPSC-derived cells [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] to assess the toxicity of the individual chemicals [ 20 , 28 , 29 , 30 , 31 , 32 ], whole mixtures [ 11 , 16 ], and complex substances [ 33 , 34 ]. The reasons we chose iPSC-derived cells are because: (i) these cells are more physiological than immortalized cell lines and can be derived for different tissues/organs [ 35 ]; (ii) they can be obtained from the same individual(s) to enable highly reproducible experiments [ 36 ]; (iii) despite some limitations with the degree of maturation, these cells compare well to primary cells in terms of their function and expected organ-specific toxicity [ 35 , 37 , 38 ]; and (iv) a small number of iPSC-derived cell types can be as informative about hazard and safety margins as the larger set of in vitro models [ 33 ], or many ToxCast bioassays [ 20 ]. Specifically, in a study of petroleum substances [ 33 ] we found that bioactivity data from four human iPSC-derived and HUVEC cells are superior to other immortalized cell lines to rank substances in a manner highly concordant with their expected in vivo hazard potential.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The framework can flexibly incorporate whatever combination(s) of data the user chooses, and the typical model is built so that a higher score translates to higher risk/concern/vulnerability/etc. The ToxPi framework has been used with a wide range of data types with many different outcomes of interest, including decision support and hazard assessment by bodies such as the International Agency for Research on Cancer and the National Academy of Sciences [ 5 7 ], environmental impact due to natural disasters [ 8 , 9 ], data-driven clustering for substances of unknown/variable composition [ 10 ], and clinical phenotype evaluation [ 11 ]. Models can be built with a user-friendly ToxPi GUI (Graphical User Interface) application [ 12 ] or the toxpiR package ( https://CRAN.R-project.org/package=toxpiR ).…”
Section: Introductionmentioning
confidence: 99%